2017
DOI: 10.1007/s11356-016-8356-8
|View full text |Cite
|
Sign up to set email alerts
|

Cr(VI) reduction and Cr(III) immobilization by resting cells of Pseudomonas aeruginosa CCTCC AB93066: spectroscopic, microscopic, and mass balance analysis

Abstract: The aim of this study was to investigate the mechanism of Cr(VI) reduction and Cr(III) immobilization by resting cells of Pseudomonas aeruginosa using batch experiments and analysis techniques. Data showed that resting cells of this strain (3.2 g/L dry weight) reduced 10 mg/L of Cr(VI) by 86% in Tris-HCl buffer solution under optimized conditions of 5 g/L of sodium acetate as an electron donor, pH of 7.0 and temperature of 37 °C within 24 h. Cr(VI) was largely converted to nontoxic Cr(III), and both soluble cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…(1) Partial Cr(VI) directly binds via electrostatic attraction to positively charged functional groups on the surface of the CUST210-1 strain (3.05%), or partial Cr(VI) is reduced to Cr(III) via membrane-associated chromate reductase or soluble chromate reductase (i.e., ChrR) and binds to negatively charged functional groups on the surface of the CUST210-1 strain (8.49%), ( 2 ). An analogous mechanism has been discovered in other bacteria, such as P. aeruginosa and S. maltophilia [14,36].…”
Section: Distribution Of Cr(vi) Reduction Products and Possible Cr(vi) Reduction Mechanismsupporting
confidence: 58%
See 1 more Smart Citation
“…(1) Partial Cr(VI) directly binds via electrostatic attraction to positively charged functional groups on the surface of the CUST210-1 strain (3.05%), or partial Cr(VI) is reduced to Cr(III) via membrane-associated chromate reductase or soluble chromate reductase (i.e., ChrR) and binds to negatively charged functional groups on the surface of the CUST210-1 strain (8.49%), ( 2 ). An analogous mechanism has been discovered in other bacteria, such as P. aeruginosa and S. maltophilia [14,36].…”
Section: Distribution Of Cr(vi) Reduction Products and Possible Cr(vi) Reduction Mechanismsupporting
confidence: 58%
“…To consider the characteristics of Cr(VI)-containing wastewater and the operational performance of the biosystem, the pH value of the experiment was controlled at 7.0. An optimal Cr(VI) reduction at pH 7.0 was determined for Bacillus sp., P. aeruginosa, and S. maltophilia [14,36,41]. The decrease in Cr(VI) reduction efficiency at pH 9.0 was mainly attributed to the possibility that deviation from appropriate pH values may affect the degree of ionization of ChrR [36].…”
Section: Effects Of Operating Parameters On Continuous Cr(vi) Removal By Immobilized Ochrobactrum Sp Cust210-1 Biosystemmentioning
confidence: 99%
“…Furthermore, Cr (VI) reduction potential of cells under nongrowth conditions was evaluated to explore possibility for field scale. In earlier studies resting cells of P. aeruginosa CCTCC AB93066 were able to achieve 86% reduction of 10 mg l −1 of Cr (VI) in Tris‐HCl buffer solution under optimized conditions (Kang et al ) whereas Pseudomonas brassicacearum LZ‐4 cells could reduce 80% of 10 mg l −1 of Cr (VI) (Yu et al ). Recently Zeng et al () reported a novel culture Oceanobacillus oncorhynchi W4 which was able to reduce 80% of 10 mg l −1 Cr (VI) under resting cell conditions in Tris‐HCl buffer after 24 h. In this study, the resting cells of isolate M5 could tolerate five time higher concentration of Cr (VI) than reported in previous studies and afforded to reduce 22·71 ± 0·5% of 50 mg l −1 Cr (VI) in 50 mmol l −1 Tris‐HCl buffer after 20 h.…”
Section: Discussionmentioning
confidence: 99%
“…To date, various bacterial strains, including Pseudomonas sp., Enterobacter aerogenes , Serratia proteamaculans , Bacillus sp., Microbacterium sp., Trichococcus pasteurii , Desulfovibrio vulgaris , Ochrobactrum sp., Escherichia coli , Shewanella algae , Paenibacillus ferrarius , Exiguobacterium aestuarii , and Stenotrophomonas maltophilia , capable of reducing Cr(VI) to Cr(III), have been isolated from various environments under anaerobic or aerobic conditions [3,4,5,6,7,8,9]. Although most of these microbes have been isolated, the availability of high selectivity, high reducing power, broad environmental tolerance, and anaerobic Cr(VI)-reducing bacteria is a prerequisite for accurate Cr(VI) measurement from actual wastewater using microbial fuel cells (MFCs).…”
Section: Introductionmentioning
confidence: 99%